2020
DOI: 10.1007/s11357-020-00306-w
|View full text |Cite
|
Sign up to set email alerts
|

ACE2/ACE imbalance and impaired vasoreparative functions of stem/progenitor cells in aging

Abstract: Aging increases risk for ischemic vascular diseases. Bone marrow-derived hematopoietic stem/ progenitor cells (HSPCs) are known to stimulate vascular regeneration. Activation of either the Mas receptor (MasR) by angiotensin-(1-7) (Ang-(1-7)) or angiotensinconverting enzyme-2 (ACE2) stimulates vasoreparative functions in HSPCs. This study tested if aging is associated with decreased ACE2 expression in HSPCs and if Ang-(1-7) restores vasoreparative functions. Flow cytometric enumeration of Lin − CD45 low CD34 + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 58 publications
(78 reference statements)
2
14
0
Order By: Relevance
“…Furthermore, results of studies in immunosuppressed rats post-MI demonstrated that intramyocardial injection of human MSCs from old donors is less effective than those from young donors as assessed by left ventricular ejection fraction, fractional shortening, and left ventricular cavity dimensions 2 . Similarly, bone marrow-derived hematopoietic stem/progenitor cells (HSCPCs) derived from aged mice show impaired vascular repair potential compared to those isolated from young mice, a difference that correlates with lower expression of ACE2 in the aged HSCPCs 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, results of studies in immunosuppressed rats post-MI demonstrated that intramyocardial injection of human MSCs from old donors is less effective than those from young donors as assessed by left ventricular ejection fraction, fractional shortening, and left ventricular cavity dimensions 2 . Similarly, bone marrow-derived hematopoietic stem/progenitor cells (HSCPCs) derived from aged mice show impaired vascular repair potential compared to those isolated from young mice, a difference that correlates with lower expression of ACE2 in the aged HSCPCs 27 .…”
Section: Discussionmentioning
confidence: 99%
“…In the bloodstream, the level of soluble ACE2 is normally lower than 17 mU/L [117,118] but becomes elevated in different cardiovascular disorders [117][118][119][120]. Probably promoted by the SARS-CoV-2 infection, it is also raised among patients with severe COVID-19 [121], which could be more pronounced among older patients [86,119,[122][123][124]. However, contradictory results have been reported regarding circulating ACE2 activity in SARS-CoV-2 infected patients that is ranging from elevated [125][126][127][128][129][130][131] to unchanged [132,133] or even lowered circulating ACE2 levels [134].…”
Section: Renin-angiotensin System (Ras) In the Cns During Sars-cov-2 ...mentioning
confidence: 99%
“…Biological aging is traditionally thought of as the progressive loss of functional characteristics on a cellular and organismal level. Both impaired stem cell function and accumulated senescent cells contribute to this process [23][24][25][26]. Cells that reach the point of irreversible cell arrest are considered to be senescent.…”
Section: Senescence Immunity and Inflammagingmentioning
confidence: 99%